Research Gender Features of Formation of Student Life Scenarios - Vadym Zavatskyi; Ihor Zhyharenko (Vasyl Stefanyk Precarpathian National University, 2017)
The article provides an analysis of the impact on gender identity formation of student life scenarios. It is shown that socio-economic and political changes are factors which change perceptions of themselves and the general picture of the world youth, and is a catalyst for the process of finding one's own life script or harmonious way of life. The authors established that the individual life path or script must meet the abilities and capabilities of the young man and also be a means of self-realization in life. The paper stated that under current conditions the process of personal and professional self-education related to a number of difficulties, that is why the problem of forming life script personality in adolescence is becoming increasingly important. Based on the scientific approaches the problem of forming life scenarios identity and gender identity problem. We characterize the sample studied, which was caused by the objectives and purpose of the study. The article provided a description of methods by which we conducted the diagnosis of gender identity influence on the formation of individual life scenarios in adolescence. We used the results of correlation analysis.